REVENUE AND EXPENDITURE IN VILLAGE GOVERNANCE IN TONKIN IN THE EARLY 20TH CENTURY: THE CASE OF CAM KHE DISTRICT, PHU THO PROVINCE - Minh Anh, Phan (HNUE Journal of Science: Journal of Social Sciences, 2026)
In 1883 and 1884, the Nguyễn dynasty signed the Harmand and Patenôtre Treaties, after which Vietnam officially became a French colony. The French colonial administration intervened in the Vietnamese village system through the policy of village administration reform, including the reorganization of village revenues and expenditures in Tonkin. Based on more than forty reformed village regulations, this article reconstructs the financial structure of villages in Cam Khe district (Phu Tho province), a midland and mountainous area of northern Vietnam. It examines local sources of revenue, expenditure, and the mechanisms for financial management as stipulated in these conventions. The study contributes to a better understanding of French colonial administrative reform beyond the Red River Delta, highlighting both the similarities and differences between Cam Khe and other localities, as well as the coexistence of colonial financial control and traditional village self-governance.